The Truth Behind The Decision of Consumers in Buying Counterfeit Cosmetics Product: A Qualitative Phenomenological Research - Risca Kurnia Sari; Achmad Soediro; Fatchur Rochman (University of Islam Malang, 2018)
Research conducted is a type of qualitative phenomenological research that reveal and understand the meaning behind the phenomenon of the actions of individuals who perform various actions on the basis of their own perceptions as well as aspects of the background of the action. The number of informants in this study are six people. Sampling method of this study used purposive sampling with snowball sampling method. The findings shows that well recognized or reputable brand considered to be one of the reasons consumers choose to buy stimulation of brand POND’S. Marketing stimuli such as advertising on television, the product that suits consumer needs in affordable price can stimulate consumers buying decision. Low price of POND’S counterfeit product is the main considerations in encouraging buying decision. High consumer loyalty toward original POND’S brand made them decide to buy counterfeit POND’S without considering the authenticity and its side effect on consumer health. Reference groups that dominate consumer minds in buying the counterfeit POND’S product are workmate and store employees where the product is sold. Motivation in seeking new products and the high level of trust toward Unilever brand (POND’S) encourages consumers to buy counterfeit POND’S. Private sources (office colleagues) and commercial (TV advertisement) considered as main information sources for a consumer in buying POND’S and counterfeit POND’S counterfeit.